Association of Insulin Resistance with Liver Enzymes and Inflammatory Biomarkers in Patients with Metabolic-Associated Fatty Liver Disease - Shehryar Kanju, Yasir Abbas Zaidi, Shahnawaz Hassan Gardezi, M. Shakil Zari Khawri Siddiqui, Rizwan Saeed Kiani, Asma Arshad Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Metabolic-associated fatty liver disease (MAFLD) is a common chronic liver disorder closely linked with metabolic dysfunction and insulin resistance. Insulin resistance plays a central role in hepatic fat accumulation and promotes chronic low-grade inflammation, leading to hepatocellular injury. However, the relationship between insulin resistance, liver enzymes, and inflammatory biomarkers in MAFLD patients remains insufficiently explored in local clinical settings. Objective: To evaluate the association of insulin resistance with liver enzymes and inflammatory biomarkers in patients diagnosed with metabolic-associated fatty liver disease. Methods: This hospital-based cross-sectional study was conducted in the Department of Gastroenterology, Nishtar Medical University and Hospital, Multan, Pakistan, from July 2022 to July 2023. A total of 100 adult patients with ultrasound-confirmed fatty liver fulfilling MAFLD criteria were enrolled. Fasting plasma glucose and fasting insulin levels were measured, and insulin resistance was calculated using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Liver enzymes including alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and gamma-glutamyl transferase were assessed. Inflammatory biomarkers such as high-sensitivity C-reactive protein, interleukin-6, tumor necrosis factor-alpha, ferritin, and adiponectin were also measured. Patients were categorized into insulin-resistant and non–insulin-resistant groups, and statistical analysis was performed to assess group differences and correlations. Results: Insulin resistance was observed in 62% of patients. Insulin-resistant individuals exhibited significantly higher levels of liver enzymes, particularly alanine aminotransferase, aspartate aminotransferase, and gamma-glutamyl transferase, compared to non–insulin-resistant patients (p<0.001). Inflammatory biomarkers including high-sensitivity C-reactive protein, interleukin-6, tumor necrosis factor-alpha, and ferritin were significantly elevated in the insulin-resistant group, while adiponectin levels were significantly reduced (p<0.001). HOMA-IR showed significant positive correlations with liver enzymes and inflammatory markers and a negative correlation with adiponectin across both genders. Conclusion: Insulin resistance is strongly associated with hepatic enzyme abnormalities and increased systemic inflammation in patients with MAFLD. These findings emphasize the central role of insulin resistance in disease pathophysiology and support the use of metabolic and inflammatory biomarkers for improved risk stratification and management of MAFLD. Keywords: Metabolic-associated fatty liver disease; Insulin resistance; HOMA-IR; Liver enzymes; Inflammatory biomarkers; hs-CRP.